PEMBAGIAN PERAN GENDER PADA PERMAINAN TRADISIONAL PONDOK-PONDOK (DI DESA TEBING TINGGI OKURA KECAMATAN RUMBAI PESISIR KOTA PEKANBARU) - Muhammad Yazid; Hesti Asriwandari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Pondok-pondok traditional game is the imitation of gender roles in Malayfamilies, such as the role of working for the boys and the role of caring children forgirls. In this game will be the construction of traditional gender terms, this researchtook place in the Tebing Tinggi Okura Kota Pekanbaru. The purpose of this studywas to determine the division of gender roles and gender constructions that exist inthis game.The method used in this research is descriptive research method. Descriptiveresearch is research that aims to uncover the facts, circumstances, and phenomena.corelation to research by the author is the disclosure of the division of roles andgender construction in the pondok-pondok traditional game in Tebing Tinggi Okura.Therefore, the author will develop concepts, collecting data and facts that occurred inthe study area. Data collection techniques used in-depth interviews and observations,while the techniques of data analysis using descriptive qualitative data analysistechnique of Miles and Huberman, namely data collection, data reduction, datapresentation, and conclusion.Based on the implementation of the research results is, in this game there is adivision of gender roles boys mimicked the role of fathers in the public sector andgirls imitating the mother's role in the domestic sector. Games is influenced byreligion, role of parents, the local community and gender patterns. In this game thereare also values such as the value of responsibility, leadership values, the value ofHarmony, Democratic Values and Value Simplicity.Keywords: Pondok-pondok traditional game, the division of gender roles, genderconstruction